Handbook Hittite Empire (Berlin)
viii, 799 sayfa
Keywords: “This handbook offers an overview of the political, administrative and economic structure of the Hittite empire in a diachronic perspective, from the Old Kingdom untill the fall of the Hatti state. It will deal with: the relation between environment and political power; the political and administrative structure; war; religion and power“ --